Chapter The Centres of Public Power Between the Cities and the Countryside, in the Light of the Recent Archaeology (Italian Peninsula, Late 5th-9th Century) - CANTINI, FEDERICO (Firenze University Press, 2023)
The paper aims to illustrate, especially through the results of recent archaeological studies, the articulation and forms of the centres of public power between the Gothic and the Carolingian periods, in the dialectic between the city as a seat of the institutions and their protagonists, and the countryside, which contains the production centres and controls their resources. We will consider the Italian territory, with a focus on Tuscany, and propose some comparisons with the rest of Europe. An architectural, artistic and topographical resilience emerges. It is probably the consequence of the continuity of a series of elements: the public ownership of particular urban and suburban areas and palaces, as well as of rural strategic sites; the use of languages and models of the Late Roman aristocracy, and the economic impoverishment of the early medieval rulers.